Exploration of the relationship between self-compassion, alexithymia and emotion regulation in a clinical population. - Rusk, Dorothy Alice (The University of Edinburgh, 2015)
Background: Negative forms of self-relating such as self-criticism and self-judgement are known to contribute to poor mental health across diagnoses including eating disorders. Negative self-relating can lead to avoidance or suppression of emotions, and poor attachment relationships can lead to deficits in self-reassuring abilities. Self-compassion is a construct which is gaining attention in clinical research as a potentially important and healthy way of relating to the self in the face of painful or difficult experiences. Systematic review: A systematic review of the literature eating disorders and self-compassion suggested that lower levels of self-compassion are related to worse eating disorder pathology, particularly emotional eating, and body image dissatisfaction. Findings suggest that self-compassion training may have a role in multimodal prevention and treatment approaches for eating disorders, disordered eating and body image problems, particularly bulimia or binge eating disorders. The role in restrictive eating behaviour is less clear and warrants further research. Aims: This study was a cross-sectional study design with a purpose of conducting Confirmatory factor analysis on the Self-Compassion Scale – Short Form, and correlational analysis of the relationship between self-compassion, (as measured on SCS-SF) with emotion regulation difficulties, alexithymia and distress. Participants and procedure: 297 people referred to an adult clinical psychology service in Scotland completed the SCS-SF and measures of emotion regulation, alexithymia and distress. Results: CFAs did not support six factor or hierarchical models for SCS-SF. Instead a two-factor model was supported. Correlation analysis indicated that self-compassion is inversely associated with difficulties in emotion regulation, alexithymia and distress. Hierarchical regression analyses indicated that self-compassion was a unique predictor of distress. Implications: Further clarification of the construct of self-compassion, its role in psychopathology and how it should be measured is required. It is important that as research involving self-compassion and its role in mental health services progresses, that psychometrically valid measures are employed. Furthermore, correlation and regression analyses suggest convergent validity for the construct of self-compassion, and support theoretical links with emotion regulation. Conclusions: Self-compassion appears to be an important variable in eating disorders pathology and appears to be linked with adaptive emotion regulation in clinical populations. However results suggest longitudinal research and a more robust measure is required for use in clinical populations, especially if information about facets of the construct are to be understood.
Keywords: self-compassion; emotion regulation; alexithymia